International Olympic Committee (IOC) Sport Mental Health Assessment Tool 1 (SMHAT-1) and Sport Mental Health Recognition Tool 1 (SMHRT-1): towards better support of athletes' mental health. Issue 1 (18th September 2020) - Gouttebarge, Vincent; Bindra, Abhinav; Blauwet, Cheri; Campriani, Niccolo; Currie, Alan; Engebretsen, Lars; Hainline, Brian; Kroshus, Emily; McDuff, David; Mountjoy, Margo; Purcell, Rosemary; Putukian, Margot; et al.
Abstract : Objectives: To develop an assessment and recognition tool to identify elite athletes at risk for mental health symptoms and disorders. Methods: We conducted narrative and systematic reviews about mental health symptoms and disorders in active and former elite athletes. The views of active and former elite athletes (N=360) on mental health symptoms in elite sports were retrieved through an electronic questionnaire. Our group identified the objective(s), target group(s) and approach of the mental health tools. For the assessment tool, we undertook a modified Delphi consensus process and used existing validated screening instruments. Both tools were compiled during two 2-day meeting. We also explored the appropriateness and preliminary reliability and validity of the assessment tool. Sport Mental Health Assessment Tool 1 and Sport Mental Health Recognition Tool 1: The International Olympic Committee Sport Mental Health Assessment Tool 1 (SMHAT-1) was developed for sports medicine physicians and other licensed/registered health professionals to assess elite athletes (defined as professional, Olympic, Paralympic or collegiate level; aged 16 years and older) potentially at risk for or already experiencing mental health symptoms and disorders. The SMHAT-1 consists of: (i) triage with an athlete-specific screening tool, (ii) six subsequent disorder-specific screening tools and (iii) a clinical assessment (and related management) by a sports medicine physician or licensed/registered mental health professional (eg, psychiatrist and psychologist). The International Olympic Committee Sport Mental Health Recognition Tool 1 (SMHRT-1) was developed for athletes and their entourage (eg, friends, fellow athletes, family and coaches). Conclusion: The SMHAT-1 and SMHRT-1 enable that mental health symptoms and disorders in elite athletes are recognised earlier than they otherwise would. These tools should facilitate the timely referral of those athletes in need for appropriate support and treatment.